Natriuretic peptides for the treatment of acute heart failure: a focus on nesiritide in recent clinical trials. (July 2015) - Fajardo, Jeff; Heywood, J Thomas; Patterson, J Herbert; Adams, Kirkwood; Chow, Sheryl L
<x xml:space="preserve">Abstract</x> Nesiritide, a recombinant form of B-type natriuretic peptide, is a vasodilator and currently recommended as an additive therapy for patients with acute decompensated heart failure (ADHF) who have been optimized on loop diuretics. With hospitalizations for ADHF rising, appropriate selection of therapy becomes even more important to optimize efficacy and reduce adverse events. Nesiritide has many properties that antagonize the pathophysiologic processes of heart failure and has demonstrated a comparative benefit in previous reports; however, controversy still remains with respect to its efficacy and safety. Based on results from recent clinical trials, nesiritide has been shown to be safe at currently approved doses and strongly considered for the treatment of ADHF in patients who remain symptomatic despite optimal doses of intravenous loop divertics.